Variation among grain sorghum genotypes in response to nitrogen fertilizer - Mahama, George Yakubu (Kansas State University, 2012)
Grain sorghum [Sorghum bicolor (L.) Moench] is an important crop in the semi-arid regions of Africa, Asia and United States. Productivity of grain sorghum is limited by soil fertility, especially nitrogen (N). Sorghum genotypes are known to vary in their response to nitrogen, however, the information on nitrogen use efficiency (NUE) is limited. The objectives of this research were to (a) determine the response of sorghum genotypes (hybrids and inbred lines) to nitrogen fertilizer (b) quantify genotypic differences in NUE; and (c) determine physiological and morphological basis of NUE. Field experiments were conducted at three locations in Kansas (Hays, Ottawa and Manhattan) during 2010 and 2011. Six hybrids and six inbred lines of grain sorghum were grown with 0, 45 and 90 kg N ha-1.The experimental design was a split-plot design with N regimes as main plots and genotypes as sub-plot, with four replications. Planting was done in May and June across all the locations, and nitrogen fertilizer (Urea, 46% N) was applied at emergence. Data on N concentration in the leaves, stems and grain were determined. NUE and components of N use were computed for Ottawa and Manhattan as follows: Nitrogen use efficiency (NUE): Grain weight / N supplied; Nitrogen utilization efficiency: Grain weight / N total in plant; Nitrogen uptake efficiency: N total in plant / N supplied; Percent fertilizer recovery = [uptake (fertilized plot) – N uptake (un- fertilized plot)] / [ N applied ] x 100; and Nitrogen harvest index (NHI) = Grain N / N total in plant. Where N supplied = Rate of N fertilizer applied + soil N supplied. Growth and yield data were collected at all locations. There were significant effects of genotypes (P < 0.05) and nitrogen (P < 0.05) on biomass and grain yield across all locations. Performance of hybrids was generally superior to the inbred lines of all traits. Sorghum hybrids 26506 and 99480 produced maximum grain yield across all locations. While inbred lines B35 and SC35 had the lowest grain yield. Maximum biomass and grain yield was obtained at 90 kg N ha-1, followed 45 kg N ha-1, and lowest in 0 N kg ha-1. There were significant differences among genotypes for all NUE traits at Ottawa and Manhattan. Across genotypes, total NUE ranged from 17.2 to 42.6 kg kg-1, utilization efficiency from 24.3 to 60.2 kg kg-1, N uptake efficiency ranged from 56.1 to 82.5%, recovery from 2 to 52%, and NHI from 43.6 to 81.3%. Among the genotypes, 99480 and 26506 both known to be post–flowering drought tolerance were high in NUE and component of N use. While genotypes B35 and SC35 were the lowest in NUE and components of N use. Overall, our data suggest that there were significant differences for NUE traits in sorghum hybrids and inbred lines. There are opportunities to breed for higher NUE in grain sorghum.
Keywords: Nitrogen use efficiency; Agronomy (0285)